If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 6 + -3q = 1 * 1 Combine like terms: 1 + 6 = 7 7 + -3q = 1 * 1 Multiply 1 * 1 7 + -3q = 1 Solving 7 + -3q = 1 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3q = 1 + -7 Combine like terms: 7 + -7 = 0 0 + -3q = 1 + -7 -3q = 1 + -7 Combine like terms: 1 + -7 = -6 -3q = -6 Divide each side by '-3'. q = 2 Simplifying q = 2
| 0+6-3q=1*0 | | 4-2(x+3)=2x+6 | | 6-3q=1 | | x=3(0.6x) | | 6a=4a+9 | | x=2(8.0x) | | x=7(2.5x) | | x=10(3.2x) | | y/5-1x20 | | (x^8+5)*(x^12+7)=0 | | 2s=700 | | y/5-1x15 | | 3(3x-7)=26 | | 5x+18=3x+32 | | 2≥y/5−1 | | (2-5x)x(x-6)x(x+1)=0 | | 9x=642 | | (2-5x)*(x-6)*(x+1)=0 | | 2(-3)+6=0 | | (x^8+5)x(x^12+7)=0 | | (x^8+5)(x^12+7)=0 | | 28x+6=5x-40 | | 41/2x161/2÷41/2 | | X+4.5=104.8 | | 4x+4x=-8+14x | | 8sin^3x-6sinx+1=0 | | (2-5x)(x-6)(x+1)=0 | | -4x+7=9x | | (3*4*n)+n=n | | X/2=428 | | 8*3*n=24 | | 8=2/1/2x-4/1/2 |